The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1708-8208.2011.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Chipping of Zirconia‐Based and Metal–Ceramic Implant‐Supported Single Crowns

Abstract: Chipping was found to be more frequent for all-ceramic implant-supported single crowns. If the reasons for the vulnerability of all-ceramic crowns remain unknown, implants with all-ceramic single crowns should generally be recommended with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 17 publications
5
53
0
2
Order By: Relevance
“…Previous publications evaluating the same material composition (Cercon/Cercon Ceram Kiss; DeguDent, Hanau, Germany) in a comparable setup found significantly higher complication rates of 7.5% after 6 months and 24.5% after two years, respectively [9,23]. Furthermore, the patient-reported outcome was assessed in this trial [22], revealing a high patient satisfaction, as observed in the present investigation.…”
Section: Patient-reported Outcome (Vas)supporting
confidence: 82%
See 1 more Smart Citation
“…Previous publications evaluating the same material composition (Cercon/Cercon Ceram Kiss; DeguDent, Hanau, Germany) in a comparable setup found significantly higher complication rates of 7.5% after 6 months and 24.5% after two years, respectively [9,23]. Furthermore, the patient-reported outcome was assessed in this trial [22], revealing a high patient satisfaction, as observed in the present investigation.…”
Section: Patient-reported Outcome (Vas)supporting
confidence: 82%
“…Because market-available zirconia implants are mostly designed as one-piece implants comprising an endosseous, transmucosal, and intraoral part in a single piece, the restoration has to be cemented to the implant abutment comparable to tooth-supported reconstructions. Especially in posterior regions, the same polycrystalline ceramic material (Y-TZP) as used for ceramic implant production proved to be a reliable substructure for the fabrication of highly esthetic, implantsupported, bi-layer crowns [9]. For both tooth-and implant-supported, zirconia-based SCs, survival rates seem to be comparable to those of conventional porcelain-fused-to-metal (PFM) crowns [10].…”
Section: Introductionmentioning
confidence: 99%
“…Groten and Huttig [30] reported 2 ceramic veneering material chippings of 54 single crowns after 28 months which needed replacement. Nothdurft and Pospiech [35] showed 10 % and Schwarz et al [36] reported 24.5 % porcelain chipping in Cercon single crowns on implant abutments. In the study conducted by Schwarz et al [36], 11.3 % of fractures led to failure.…”
Section: Discussionmentioning
confidence: 97%
“…Over the last years, chipping of veneering ceramics has been recognized as the most frequent technical complication of allceramic single crowns (SCs) [1,2] and multiunit fixed dental prostheses (FDPs) [3][4][5][6]. Further, clinical studies indicated that fractures of the veneering ceramic were more frequent with zirconia frameworks than with conventional metal-ceramic restorations [4,7].…”
Section: Introductionmentioning
confidence: 99%